Vitamin D Status and Acute Coronary Syndrome – A Single-Centre Study (Cardiovascular Journal, 2021)
Background: Vitamin D are needed for normal functioning of cardiovascular system, and its deficiency has been linked to different cardiovascular disorders, including hypertension. However, the relationship between vitamin D deficiency and ischaemic heart disease is not yet clear. The present study was intended to find out the association between serum vitamin D level and acute coronary syndrome (ACS).Methods: The cross-sectional analytical study was carried out in a tertiary care hospital of Dhaka, Bangladesh. Fifty-one consecutive ACS patients admitted into the Department of Cardiology of the hospital were considered as the cases and 51 apparently healthy subjects were considered as the controls. The exposure and outcome variables were serum vitamin D and ACS respectively. Vitamin D insufficiency and deficiency were defined as serum 25(OH) D